Reclamation Responsibility for Illegal Mining in Indonesia: how should it be? - Rohmadanti, Ira Fadila; Rafiqi, Ilham Dwi; Desta Saputra, I Kadek Ramadana Vikram; Akhilesh Kumar (Universitas Muhammadiyah Malang, 2023)
Abstract Illegal mining is one of the problems in natural resource management in Indonesia. The enactment of Law Number 3 of 2020 concerning the Amendment to Law Number 4/2009 concerning Mineral and Coal Mining (UU No. 4/2009) further strengthens the concept of ecosystem protection, one of which is through reclamation and post-mining obligations. However, in the current law, there is confusion regarding the assignment of reclamation responsibility. The purpose of this paper is to examine how the concept of legal responsibility for illegal mining, and provide justification or consideration of the urgency of reclamation responsibility for illegal mining. This research employed a normative method and statutory, case, and conceptual approaches. The results of the study indicate that there is a legal vacuum in the current mining regulations regarding reclamation responsibility for illegal mining. The concept of responsibility for reclamation in Law no. 3/2020 is only charged to legal mining but does not cover illegal mining, causing many mine pits to be left unattended, and this situation has claimed many lives. Parties involved in Illegal mining in Indonesia should not only be burdened with liability but also environmental obligations or responsibilities in the form of reclamation and post-mining from illegal mining activities carried out. The first thing that can be done by the Government is to amend Law No. 3/2020 by expanding the concept of recovery responsibility to ensure that it can cover illegal mining. The imposition of reclamation responsibility for illegal mining is expected to provide maximum recovery for the ecosystem around the former mine. Abstrak Pertambangan ilegal merupakan salah satu masalah dalam pengelolaan sumber daya alam di Indonesia. Lahirnya Undang-Undang Nomor 3 Tahun 2020 tentang Perubahan Atas Undang- Pertambangan Mineral dan Batubara sebelumnya (UU No. 4/2009) semakin memperkuat konsep perlindungan ekosistem salah satunya melalui kewajiban reklamasi dan pasca tambang. Akan tetapi, dalam aturan hukum saat ini terdapat kerancuan mengenai pembebanan tanggung jawab reklamasi. Tujuan penulisan ini adalah untuk mengkaji bagaimana konsep pertanggungjawaban hukum pertambangan ilegal, dan memberikan justifikasi atau pertimbangan urgensi tanggung jawab reklamasi untuk pertambangan ilegal. Metode penelitian dalam penelitian ini adalah penelitian normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan konseptual. Hasil penelitian menunjukkan bahwa terdapat kekosongan hukum (legal vacuum) dalam aturan pertambangan saat ini mengenai tanggung jawab reklamasi bagi pertambangan ilegal. Konsep tanggung jawab reklamasi dalam UU No. 3/2020 hanya dibebankan kepada pertambangan legal namun tidak menjangkau pertambangan ilegal. Hal ini menyebabkan banyak lubang tambang yang dibiarkan yang merenggut banyak korban jiwa. Pelaku pertambangan ilegal di Indonesia seharusnya tidak hanya dibebani tanggung jawab pidana, melainkan kewajiban atau tanggung jawab lingkungan dalam bentuk reklamasi dan pasca tambang dari kegiatan tambang ilegal yang dilakukan. Hal pertama yang dapat dilakukan oleh Pemerintah adalah melakukan perubahan terhadap UU No. 3/2020 dengan memperluas konsep tanggung jawab pemulihan sehingga dapat juga menjangkau pertambangan ilegal. Pembebanan tanggung jawab reklamasi bagi pertambangan ilegal ini diharapkan dapat memberikan pemulihan yang maksimal bagi ekosistem sekitar bekas tambang.